Comportamento dos docentes e discentes, com foco nas experiências e competências relacionadas à economia criativa, que podem complementar o ensino de administração - Moreira, Karina Bitelli Scholl de Figueiredo (2024)
The present study aims to identify the behaviors, similarities and differences related to the Creative Economy, of students and teachers at private Administration colleges in Rio. To achieve this purpose, the methodology used was a document analysis and a content analysis, consisting of six categories, obtained from in-depth interviews. The analysis of the data obtained indicated the respective convictions of teachers and students about the motivations when making their choices about course and faculty; perceptions regarding curriculum of the Administration course; the infrastructure and characteristics of the higher education institution; with regard to teaching and assessment methods; and in relation to skills and experiences. The managerial implications of this study are: the collection and analysis of useful information for the implementation of positive changes for faculties, both in the physical aspect of the institution and in the subjects and skills to be taught; and facilitating how colleges can promote their brand and target their marketing